Implementation of Corporate Social Responsibility (CSR) in Improving Environmental Performance and its Impact on Green Accounting and Green Innovation - Nurdiniah, Dade; Putri, Sri Yuli Ayu; Novialumi, Anita; Febryan, Ajran (International Journal of Energy Economics and Policy, 2025)
This study was conducted to examine the effect of CSR implementation on environmental performance and to examine its impact on green accounting and green innovation. The research method used a quantitative approach with secondary data obtained from annual reports and sustainability reports of manufacturing companies in Indonesia listed on the Indonesia Stock Exchange (IDX) for the 2020-2024 period. Sampling was conducted using purposive sampling, obtaining 325 companies as samples. The analysis results show that CSR implementation has a significant positive effect on environmental performance but does not affect green accounting or green innovation. Green accounting has been shown to have a significant effect on environmental performance and acts as a mediator between CSR and environmental performance, while green innovation does not show a significant effect either directly or indirectly. These findings confirm that the improvement in environmental performance of manufacturing companies is more supported by the integration of CSR with green accounting practices, while the contribution of green innovation is still not optimal.